When the people speak : deliberative democracy and public consultation - Fishkin, James S. (Oxford University Press, 2009)
All over the world democratic reforms have brought power to the people-but under conditions where the people have little opportunity to think about the power that they exercise. Do we want a democracy inspired by Madison or by Madison Avenue? A democracy animated by deliberation or by manipulation? This book examines each of the principal democratic theories and makes the case for a democracy in which the people offer informed judgments about politics or policy. It then goes on toshow how this form of democracy can be made a reality. When the People Speak describes deliberative democracy proje.